CONSTRUCTING RULE AND RELIGION: A HISTORICAL STUDY OF CULTURAL SYNTHESIS AND IDENTITY FORMATION IN THE SOCIO-POLITICAL ORDER OF MEDIEVAL ASSAM - Pathak, Guptajit (International Journal of Research -GRANTHAALAYAH, 2019)
The intricate relationship between religion and authority in medieval Assam is thoroughly and methodically examined in this research, with an emphasis on how identity creation and cultural synthesis shaped the region’s sociopolitical structure. Medieval Assam offers a unique historical setting where religious movements, particularly Neo-Vaishnavism, and political authority interacted to create a unique cultural matrix that both supported and legitimized rule. The study looks at how leaders merged many ethnic traditions and intentionally supported religious organizations to create a sociopolitical structure that was inclusive and promoted vibrant cross-cultural interactions. The paper advances our knowledge of the processes by which political authority and religion came together to create durable social structures and cultural identities in medieval Assam.1 In order to provide an interdisciplinary study of medieval society of Assam, the investigation consults a variety of historiographical sources, epigraphic documents, and cultural artifacts in addition to current scholarly interpretations. It emphasizes how political aspirations to reshape Assamese identity and government collided with religious changes, especially under Srimanta Sankardeva’s Neo-Vaishnavism. According to the report, cultural institutions like Namghars and Sattras play a vital role in mediating between society and the state while fulfilling both administrative and spiritual purposes. According to this essay, the sociopolitical structure of medieval Assam was a negotiated creation influenced by the interaction of political pragmatism, religion, and culture rather than a rigid imposition.